Efficacy and manner of execution of the serve in top-level women's beach volleyball players - Ana B. López Martínez; José M. Palao; Henrique Ortega; António García de Alcaraz (Revista da Educação Física)
The study of the manner of execution (technique, and spatial aspects) can provide useful information to understand the game dynamics in beach volleyball and to obtain references values for the analysis of the game and the establishment of training goals. The aim of the study was to determine the influence of the manner of execution on serve and rally performance in elite women's beach volleyball players. A total of 3,009 serves from 44 women’s players were analyzed. The variables studied were: serve technique, serve zone, serve destination, serve performance, and rally performance. An observational punctual, nomothetic, multidimensional, and intragroup design was used. A descriptive and inferential analysis of the data (Chi-Square Test) was done using SPSS v.21.0 software. The level of significance was set at p < .05. The manner of execution influences the serve performance. The jump float serve was the most used. The most effective destination was the zone between players, probability due to the players' displacement and interference between them. An absence of association between serve technique and rally performance was found. These findings showed possible connections between the way of executing the serve with the following actions done by the players and the players' strategies to control their physical load. These values may be useful to guide to players training, or to evaluate players in competition.